An appraisal of the use of an infrared digital monitoring system for long-term measurement of heart rate in reptilian embryos - Sartori, Marina R. [UNESP]; Taylor, Edwin W. [UNESP]; Abe, Augusto S. [UNESP]; Crossley, Dane A. (Elsevier B.V., 2015)
Measurement of heart rate (f(H)) in embryonic reptiles has previously imposed some degree of invasive treatment on the developing embryo. Recently a non-invasive technique of f(H) detection from intact eggs was developed for commercial avian breeders and has since been used in biological research. This device uses infrared light, enabling it to detect heartbeats in very early embryos. However, infrared light is a source of heat and extended enclosure of an egg in the device is likely to affect temperature with consequent effects on physiological processes, including f(H). We studied the effect of use of the monitor on the temperature of eggs and on fH in two species of reptiles, the snapping turtle (Chelydra serpentina) and the green iguana (Iguana iguana). Egg temperature increased from a room temperature of 27-28 degrees C, by 26% in turtles and 14% in iguanas over 1 h of enclosure, resulting in an increase in f(H) of 76-81% in turtles and 35-50% iguanas. These effects on f(H) can either be avoided by brief enclosure of each egg in the monitor or measured and accounted for during the design of long-term experiments. (C) 2015 Elsevier Inc. All rights reserved.
Keywords: Reptiles; Embryonic development; Heart rate; Buddy (R); Infrared radiation; Temperature